Positive Politeness Strategies in YouTube Comments: A Pragmatic Analysis of Kendrick Lamar’s “Money Trees” - Nesia Monika; Afriana (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study examines the application of positive politeness methods in the YouTube comment area of Kendrick Lamar’s